EXTRACTION OF LEAD (II) IONS USING DITHIZONE METHOD ON WASTEWATER OF KHONDZA (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This paper studies methods of lead and zinc metal ions extraction by dithizone from Khondzha wastewater samples. Inorganic metals or ions can act back with dithizone to produce colourful coordination. The dithizone reagent is highly sensitive to the presence of heavy metals such as lead (Pb) and zinc (Zn) as designated in this study. Inorganic metals or ionic can react with dithizone to produce coloured coordination compounds. The resulting dithizoneate may be extracted with an organic solvent such as carbon tetrachloride (CCl4). This study also involves adjusting the pH value to produce our desired dithizone metal product.  The dithizone extraction method used in extracting the Pb element indicates a good performance.